Kesadaran Karier Yang Berkaitan Dengan Fenomena Media Sosial Siswa Madrasah Tsanawiyah - Nuroniah, Pepi (Universitas Muria Kudus, 2018)
Based on the data obtained in the field there are several things: (1) there are students who already know the definition of career (2) there are students who already have career goals targeted (3) there are students who are still confused with the career to go (4) ) Career awareness of the environment, characterization and experience, (4) social media is not very influential because both in the home and school use hp restricted 5) the role of home environment, school and penokohan as well as interaction in it that contribute as contributing factors in the formation career awareness, (4) the same perspective on the use and meaning of social media and career awareness. This research uses descriptive qualitative method. The data obtained through the in-depth interview is then analyzed by phenomenology analysis technique. The interpretation of informants on career awareness based on interest, exciting, tasty, there are challenges, easy, can help and benefit to the perceived fellow in the participant's environment. The presumption and meaning of partispan to social media serves to communicate, seek information and entertainment.